Tradisi “Ngayah” pada Masyarakat Bali: Nilai-nilai Keberagaman dan Keberlanjutan Budaya di Kecamatan Landono Kabupaten Konawe Selatan Sulawesi Tenggara - Hasan, Hasni; Daus, Rahman; Sevita, Putu; Fauzi, Ahmad Rizky; Wahidin, La Ode (Tambo: Journal of Manuscript and Oral Tradition, 2025)
This paper aims to describe the values contained in the "ngayah" tradition in the Balinese Community in Landono District, South Konawe Regency, and to explain the strategies for its preservation and sustainability. The Ngayah tradition is a form of mutual cooperation and selfless devotion, has strong cultural roots in the traditions of the Balinese Community in Landono District. This paper uses a multidimensional approach to understand the social, cultural, and spiritual dimensions of the ngayah tradition. This tradition shows that the values contained in the ngayah tradition include tolerance in diversity, brotherhood, and spirituality. Ngayah functions as a medium to strengthen relationships between individuals, build solidarity across religions and cultures, and create a harmonious environment. The Ngayah tradition is an inspiration for other communities in maintaining diversity and preserving cultural traditions in the modern era. This paper is expected to provide insight and recommendations for the preservation of the sustainable Ngayah Tradition.